Overcoming smallness: Qatar, the United Arab Emirates and strategic realignment in the Gulf - Rory Miller (12489124) (2019)
Geography and the anarchic state system incentivise the United Arab Emirates (UAE) and Qatar to collaborate in managing the threat posed by being neighbours of two (aspiring) regional hegemons, Saudi Arabia and Iran. However, both small states have responded very differently to the causes and consequences of instability in the Gulf region and developed very different foreign policies to deal with their structural IR problem. Just how divergent their external relations now are is clearly seen in the UAE’s lead role in the diplomatic boycott and economic embargo launched against Qatar in June 2017—including the de facto dissolution of the Gulf Cooperation Council. Framing our examination in the theoretical literature on small states, we explain the ultimately colliding foreign policy trajectories of the UAE and Qatar in terms of diverging ideational and strategic considerations in the cause of what we term ‘overcoming smallness’. Other Information Published in: International Politics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1057/s41311-019-00180-0